Factors Influencing Malnutrition among Young Children in a Rural Community of Sarawak - Eunice, MJ; Cheah, W.L; Lee, P.Y (Mal J Nutr, 2014)
factors influencing malnutrition among children aged five years and below in Serian District of Sarawak, a district where the majority of people are indigenous. Methods: Using a cross-sectional method, a total of 177 children were randomly selected and assessed, and their mothers or caregivers were interviewed. Data were collected using a pretested questionnaire; anthropometric measurements were also taken. Data were analysed using SPSS version 17.0. Results: The prevalence of underweight, stunting and wasting in children aged five years and below was 20.9%, 11.9% and 10.2% respectively. The results suggest that the significant factors contributing to underweight are birth weight, frequency of child visit to the clinic, and individual insecurity. Only age, when complementary diet was introduced, was found to be significantly associated with stunting. For wasting, individual insecurity, duration of family planning and met recommended protein intake per day were found to be significant factors. Conclusion: The prevalence of malnutrition in children 5 years and below in Serian District of Sarawak is high compared to state figures. The major contributing factors were found to be manifested at the individual and family level. There is a need for appropriate public health promotion and socioeconomic improvement interventions towards improving the nutritional status and health of children in Serian District.